2018
DOI: 10.1080/09603123.2018.1504897
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acetamiprid on the immature murine testes

Abstract: Neonicotinoids, such as acetamiprid (ACE), a pesticide used worldwide, are believed to be safe for human use. These molecules are structurally similar to nicotine, act as nicotinic acetylcholine receptor (nAChR) agonists, and were shown to be associated with neuromuscular and reproductive disorders, but these experiments were primarily performed in mature animals. In this study, the effects of ACE on the testes of immature mice were examined. The exposure of 3-week-old mice to ACE-containing water for 180 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Five in vivo experimental studies were notified. The assessment endpoints categories identified were neurotoxicity (RefID 4 – Terayama et al, 2016 ), endocrine disruption (RefID 2 – Kong et al, 2017 and RefID 5 – Terayama et al, 2018 ), immunotoxicity (RefID 3 – Marzouki et al, 2017 ) and DNT (RefID 6 – Kagawa and Nagao, 2018 ).…”
Section: Human Healthmentioning
confidence: 99%
See 4 more Smart Citations
“…Five in vivo experimental studies were notified. The assessment endpoints categories identified were neurotoxicity (RefID 4 – Terayama et al, 2016 ), endocrine disruption (RefID 2 – Kong et al, 2017 and RefID 5 – Terayama et al, 2018 ), immunotoxicity (RefID 3 – Marzouki et al, 2017 ) and DNT (RefID 6 – Kagawa and Nagao, 2018 ).…”
Section: Human Healthmentioning
confidence: 99%
“…Therefore, it was concluded that an EKE was needed to assess the impact of the new submitted studies on the current EFSA and ECHA conclusions. Two in vivo studies in animals provided relevant data (Kong et al, 2017 ; Terayama et al, 2018 ). The analysis of the data for the assessment endpoint category endocrine disruption showed that there is uncertainty on how the systemic toxicity in these two studies was evaluated and its impact on endocrine function was not assessed.…”
Section: Human Healthmentioning
confidence: 99%
See 3 more Smart Citations